[1, 2, 4]Triazolo[4, 3-c]quinazoline and bis([1, 2, 4]triazolo)[4, 3-a:4′, 3′-c]quinazoline derived DNA intercalators: Design, synthesis, in silico ADMET profile, molecular docking and anti-proliferative evaluation studies. (15th January 2021) - El-Adl, Khaled; Ibrahim, Mohamed-Kamal; Alesawy, Mohammed S.I.; Eissa, Ibrahim H.
Graphical abstract: Highlights: Fifteen novel [1, 2, 4]triazolo[4, 3- c ]quinazoline and bis([1, 2, 4]triazolo)[4, 3-a:4′, 3′-c]quinazoline derivatives were designed and synthesized. In vitro cytotoxic activities were evaluated against two human cell lines HepG2, and HCT-116. In vitro DNA-binding was carried out for the most potent nine compounds. ADMET profile and Molecular docking studies were carried out. Abstract: In view of their DNA intercalation activities as anticancer agents, novel fifteen [1, 2, 4]triazolo[4, 3- c ]quinazoline and bis([1, 2, 4]triazolo)[4, 3-a:4′, 3′-c]quinazoline derivatives have been designed, synthesized and evaluated against HepG2 and HCT-116. The molecular design was performed to investigate the binding mode of the proposed compounds with DNA active site. The data obtained from biological testing highly correlated with that obtained from molecular modeling studies. HCT-116 was found to be more sensitive cell lines to the influence of the new derivatives. In particular, compounds 16, 18, 11 and 5 were found to be the most potent derivatives with IC50  = 3.61, 6.72, 7.16 and 5.18 µM respectively against HepG2 cell line. Also, compounds 16, 18, 11 and 5 displayed IC50  = 2.85, 3.82, 4.97 and 6.40 µM respectively against HCT-116 cell line. These derivatives displayed higher activities than doxorubicin, (IC50  = 7.94 and 8.07 µM respectively) against the two HepG2 and HCT-116 cell lines. The most active anti-proliferative derivatives 5, 6, 10, 11, 13, 16, 18, 19 and 20 were further evaluated for their DNA-binding affinity which revealed the ability of these compounds to intercalate DNA. The tested compounds displayed very strong to moderate DNA-binding affinities. Compounds 16 and 18 potently intercalate DNA at IC50 values of 26.03 and 28.37 µM respectively which were lower than IC50 of Doxorubicin (IC50  = 31.27). This finding indicated that these derivatives exhibited higher DNA binding activities than Doxorubicin . Also, compounds 11 and 5 displayed very strong DNA binding at IC50  = 30.84 and 33.56 µM respectively, which were nearly equipotent to that of doxorubicin. Moreover, most of our derivatives exhibited good ADMET profile.